Pengolahan Sampah Berbasis 5R (Reduce, Reuse, Recycle, Replace, Replant) Sebagai Implementasi Mata Kuliah Kewarganegaraan Di SD Negeri 137 Palembang - Meiwinda, Eka RIzki; Fadhli, Muhammad; Hasibuan, Rahmawaty; Zikri, Ahmad (Universitas Dehasen Bengkulu, 2024)
As a society that is a nation and a state, we must have a character to be realized which is sourced from the noble values ​​of the nation guided by Pancasila and the 1945 Constitution. Among the concepts of its implementation are listed in the citizenship course. In the implementation of the citizenship course is to implement waste management based on 5R (reduce, reuse, recycle, replace, replant). This service aims to educate students, teachers and staff at SD Negeri 137 Palembang about the importance of responsible waste management and introduce 5R practices that can be applied in the school environment. During the activity, participants will actively participate in the activities of reducing, using, reusing, replacing and replanting and learning the benefits and process of implementing 5R in schools. The result of this service is the implementation of character building for students so that they understand the concept of waste management so that they can be more sensitive, intelligent, and skilled in utilizing and utilizing the resources they have to be smart in managing waste.